English Language Teachers Adaptation to New Media Tools: A Study of Alvan Ikoku Federal College of Education Owerri - Chioma Winner Onyeama; Ifeyinwa Juliana Umeh; Stella D. Uzomah (International Journal of Global Sustainable Research, 2025)
This study applies Siemens connectivism theory and Rogers diffusion and innovation approach to examine how English language instructors at Alvan Ikoku Federal College of Education Owerri have adapted to new media tools in teaching and learning. Nigerian public schools including Alvan Ikoku face difficulties in making the shift from traditional teaching methods to 21st-century blended learning, despite the global trend of integrating media tools in education. The study, which is led by a review of the literature, randomly sampled 50 English language teachers in the School of Languages and General Studies. It finds that the school's attempts are hampered by the teachers' failure to incorporate new media tools. In order to be in line with international educational practices, the study advises stakeholders including the Teachers Registration Council of Nigeria (TRCN) to give blended learning training for educators at all levels top priority